Intravenous Propofol Versus Volatile Anesthetics For Stroke Endovascular Thrombectomy. Issue 1 (January 2021) - Diprose, William K.; Wang, Michael T.M.; Campbell, Doug; Sutcliffe, James A.; McFetridge, Andrew; Chiou, Daniel; Lai, Joshua; Barber, P. Alan
Abstract : Background: The choice of anesthetic technique for ischemic stroke patients undergoing endovascular thrombectomy is controversial. Intravenous propofol and volatile inhalational general anesthetic agents have differing effects on cerebral hemodynamics, which may affect ischemic brain tissue and clinical outcome. We compared outcomes in patients undergoing endovascular thrombectomy with general anesthesia who were treated with propofol or volatile agents. Methods: Consecutive endovascular thrombectomy patients treated using general anesthesia were identified from our prospective database. Baseline patient characteristics, anesthetic agent, and clinical outcomes were recorded. Functional independence at 3 months was defined as a modified Rankin Scale of 0 to 2. Results: There were 313 patients (182 [58.1%] men; mean±SD age, 64.7±15.9 y; 257 [82%] anterior circulation), of whom 254 (81%) received volatile inhalational (desflurane or sevoflurane), and 59 (19%) received intravenous propofol general anesthesia. Patients with propofol anesthesia had more ischemic heart disease, higher baseline National Institutes of Health Stroke Scale scores, more basilar artery occlusion, and were less likely to be treated with intravenous thrombolysis. Multivariable logistic regression analysis showed that propofol anesthesia was associated with improved functional independence at 3 months (odds ratio=2.65; 95% confidence interval, 1.14-6.22; P =0.03) and a nonsignificant trend toward reduced 3-month mortality (odds ratio=0.37; 95% CI, 0.12-1.10; P =0.07). Conclusion: In stroke patients undergoing endovascular thrombectomy treated using general anesthesia, there may be a differential effect between intravenous propofol and volatile inhalational agents. These results should be considered hypothesis-generating and be tested in future randomized controlled trials. Abstract : Supplemental Digital Content is available in the text.